Pengembangan Perangkat Pembelajaran Matematika Realistik di Sekolah Menengah Pertama - Usman Mulbar (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD FILEThe aim of the research was to produce a good quality of realistic mathematics instructional package at the Junior High School in Makassar. This study was a qualitative research which preceded by developing a realistic mathematics instructional package (PMR Package). The development of the PMR package was employed based on instructional system which developed by Thiagarajan’s et al. (1974). The development phases which took place were: (1) defining phase, (2) designing phase, and (3) developing phase. Key words: Development, mathematics education, realistic